Sun-climate connection over the last millennium facts and questions - Ogurtsov, Maxim (Bentham Science Publishers, 2014)
This eBook presents fundamental information about the solar activity, space weather, terrestrial climates and their variations over an extended period of time. The eBook provides useful facts for researchers seeking information on climate and space research with respect to solar phenomena.